Identification of arbuscular mycorrhizal fungi in plantain producing municipalities in department of Cordoba, Colombia (2018)
Currently plantain cultivation makes excessive use of agrochemicals, condition that threatens a sustainable production system and leads to the degradation of the environment, reducing the quality of the products. Based on the foregoing, and in order to expand knowledge of the arbuscular mycorrhizal fungi associated with plantain cultivation, the aim of this study was to isolate and identify fungal morphotypes that form symbiosis with plantain (Musa AAB Simmonds cv. Hartón), in farms from seven municipalities of the department of Córdoba, Colombia. In each farm, soil samples from the first 20 cm of soil depth in the rhizosphere area were taken to the soil laboratory at Universidad de Córdoba, Colombia, where spores were extracted using the OHM and the Jemkins modified methods, grounded on wet sieving in sucrose gradient. Morphological identification of the species was carried out taking into account spores characteristics, and evaluating the following parameters: number of spores of arbuscular mycorrhizal fungi (AMF), relative abundance, and diversity and dominance indexes. In seven localities, the genera Glomus, Acaulospora and Scutellospora were found. The most abundant genus was Glomus, recording for G. morphospecies 02 the highest number of spores, followed by G. deserticola. The municipalities with highest number of spores were Lorica and Moñitos, while the ones with the lowest amount were Tierralta and Valencia.